Spin foam models for 3D quantum geometry - Dowdall, R. J. (2011)
Various aspects of three-dimensional spin foam models for quantum gravity are discussed. Spin foam models and graphical calculus are introduced via the Ponzano-Regge model for 3d gravity and some important properties of this model are described. The asymptotic formula for the 6j symbol found by Ponzano and Regge is generalised to include the Ponzano-Regge amplitude for triangulations of handlebodies. Some simple observables are computed in a model for fermions coupled to 3d gravity. The result is a sum over spin foam models with certain vertex amplitudes which are described. An explicit example is given and the vertex amplitudes expressed in terms of 6j symbols. Finally, a group field theory for this spin foam model is described.